Forage grass management using treated cassava wastewater in Kalasin, Thailand - KHEMIKA CHINNABUTR; SUPAPORN POUNGCHOMPU (Asian Journal of Agriculture, 2025)
Abstract. Chinnabutr K, Poungchompu S. 2025. Forage grass management using treated cassava wastewater in Kalasin, Thailand. Asian J Agric 9: 645-652. At present, both small and large-scale farmers have been widely using forage grass production for animal feed, which can effectively reduce the cost of animal production and improve feed availability throughout the year. This study evaluates the economic benefits of using treated cassava wastewater for forage grass production in Kalasin Province, Thailand. Surveys were conducted during the 2021-2022 crop season with 90 farmers, including 50 users with treated wastewater and 40 farmers dependent on other water sources. Data was analyzed using descriptive statistics and an independent t-test. The results showed that farmers using treated wastewater obtained higher yields (36,253.882 kg/ha) and lower production costs (578.352 US$/ha) compared with non-users (25,035.751 kg/ha; 731.244 US$/ha). Net returns were also significantly higher among users (1,089.327 US$/ha or 0.030 US$/kg) than non-users (470.472 US$/ha or 0.019 US$/kg). Statistical analysis showed that yield (t = 3.19, p<0.05), cost (t = 1.79, p<0.01), and profit (t = 4.29, p<0.01) had significant differences. In addition, treatment was found to reduce fertilizer costs for farmers using wastewater by 150.50 US$/ha and enable them to sustain pastures into the dry season. This result clearly indicates that wastewater reuse is both cost-effective and environmentally friendly. This not only minimizes input costs and increases profitability, but also serves as a nature-based solution in support of year-round forage production in sustainable cassava-based farming systems.